2005
DOI: 10.1111/j.1365-2915.2005.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular comparison of host‐derived populations of parasitic Psoroptes mites

Abstract: Infestation by parasitic Psoroptes mites (Acari: Psoroptidae) is an important cause of economic loss and welfare problems in livestock in many areas of the world. At least five species within this genus have been recognized, based on the host infested, the infestation site and differences in length of the opisthosomal setae of adult male mites. Here the integrity of these species is considered by subjecting populations of mites from a range of host species and geographical locations to simultaneous morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 40 publications
0
23
2
1
Order By: Relevance
“…otsuka et al 1999, van Niekerk et al 2004, otranto et al 2005, Pegler et al 2005, Harper et al 2009, Vrijenhoek 2009, Wilson et al 2010.…”
unclassified
“…otsuka et al 1999, van Niekerk et al 2004, otranto et al 2005, Pegler et al 2005, Harper et al 2009, Vrijenhoek 2009, Wilson et al 2010.…”
unclassified
“…Thus, cross-contamination between species could not be avoided (Khaing et al 2014); (2) The gene used for molecular identification is usually single. Most studies involve the ITS2 gene (Zahler et al 1998;Essig et al 1999;Ochs et al 1999;Lohse et al 2002;Noge et al 2005;Pegler et al 2005;Hestvik et al 2007;Jia et al 2008), which cannot objectively reflect the evolution between species. The species evolution is imbalance for different genes based on the fact that rDNA ITS2 is not as good as mtDNA COI in the molecular classification and identification of Sarcoptes mites confirmed by our previous studies (Zhao et al 2015); (3) The mtDNA COI is the most common target gene used for identification at species level.…”
Section: Introductionmentioning
confidence: 97%
“…Several species that could not be classified based on morphology have now been categorized based on their DNA sequences. In Psoroptes, using ribosomal DNA internal transcribed spacers 2 (rDNA ITS2) as a molecular marker, it has been suggested that Psoroptes mites parasitizing domestic rabbit, sheep, alpaca, goat, cow, big-horn sheep, mule deer, elk, and white-tailed deer belong to the same species without host specificity (Pegler et al 2005). Using mitochondrial DNA cytochrome oxidase 1 (mtDNA COI) and 18S rDNA, Wang et al (2012) suggested that Psoroptes mites parasitizing buffalo belonged to a distinct species.…”
Section: Introductionmentioning
confidence: 99%
“…Among the five species of this genus (Sweatman 1958), Psoroptes ovis and Psoroptes cuniculi are of major veterinary importance (Wrenn 1996). Although there are some differences (Ochs et al 1999), at present, P. ovis and P. cuniculi are believed to be conspecific (Bates 1999;Zahler et al 1998Zahler et al , 2000Pegler et al 2005).…”
Section: Introductionmentioning
confidence: 98%